154 Working in partnership in the community: our experience and outcomes of the london ambulance service calls to st luke's hospice (harrow and brent) single point of access service. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Carrigan, R; Anderson, R; Tipping, I; Archer, J; Daniels, C
Abstract : In May 2015, St Luke's Hospice launched a Single Point of Access (SPA) telephone and triage service. The aim of this service was to provide a coordinated 24/7 telephone service to provide specialist advice and assistance to patients in the last year of life. The SPA is also available to health and social care professionals, including paramedics from London Ambulance Service (LAS). The SPA service also provides access to a rapid response team to provide direct care to patients in need between 7 am-to-11 pm. All telephone calls made between the SPA and LAS paramedics were logged onto a clinical database (iCare). By searching for the appropriate call code, relevant calls from the first 20 months of the SPA service were identified and analysed. There were 130 telephone calls; 90 were regarding patients known to the SPA (67 individual patients), and 40 were about patients previously unknown to the service. Taking into account multiple calls for the same event, 74 separate clinical events were analysed. The most common outcome of a call from LAS was to arrange a call/visit from a GP (usually out of hours) or by a district nurse (DN) (in or out of hours) 28%. A further 12% of the calls required a visit from the hospice rapid response team, and only 11% of patients were escorted to hospital. Analysis of these calls highlights the importance of the SPA as a liaison service, with over 25% of calls resulting in call-outs from community services (GP, DN, community palliative teams), and a further 12% requiring a call-out from the SPA rapid response team. We believe this is the first collection of data to show the impact of a palliative SPA service on the LAS, facilitating clinical decision-making, and improving confidence in leaving patients at home with community support.